Do fins alter spatiotemporal and physiological variables in front-crawl all-out effort - de Matos, C. C.; Franken, M.; Zacca, R.; Teixeira, B. C.; de Souza Castro, F. A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Fins are used in swimming training sessions for different purposes. The aim of this study was to identify and to compare the spatiotemporal and physiological parameters obtained with and without fins of 488 cm 2 area in maximal intensities of front crawl swimming. Eleven male swimmers performed two 50 m all-out in front crawl stroke, with (WF) and without fins (WOF). Swimming velocity (SV), stroke rate (SR), stroke length (SL), duration of stroke phases (A, B, C, D, propulsive and not propulsive on breathing side and opposite to breathing side) and index of coordination on both, breathing (ldC 1) and opposite of breathing side (ldC 2), number of kicks (NF), right feet deep (FRD) and left feet deep (FLD) were obtained by manuals time keepers and camcorders (60Hz). Lactate concentration [LA) and perceived exertion (PE) were assessed. Foots area were estimated. Fins increased 25% of the foot's area compared to WOF. An increase in SV was observed when compared WP to WOF. With the use of fins athletes can perform greater propulsive forces due greater contact area with the water in comparison to the area of the foot, increasing (1) propulsive momentum, (2) volume of water displacement and (3) body alignment. Fins with area of 488 cm 2 may cause limited alterations in spatia-temporal parameters.